Study age ranges and parents treatment corelation With Sibling Rivalry of childhood at Kasih Ibu kindergarden Surabaya - Firdaus, Firdaus; Fitriasari, Andikawati (PROCEEDING SURABAYA INTERNATIONAL HEALTH CONFERENCE 2019, 2020)
Sibling rivalry can impact children's social and emotional development. Children will become bedwetting, spoiled, naughty, it is done because they want to get the attention of their parents. The aims of this study was to determine the corelation of age range and parents treatment With Sibling Rivalry of childhood at Kasih Ibu Kindergarden Surabaya. This research used cross sectional design, the population was parents with more than one toddler who attended Kasih Ibu Kindergarden Surabaya. Data was taken by using simple random sampling and it got 37 respondents. Data was analyzed by spearman test. The results showed that there is significant correlation of age range parents treatment with sibling rivalry. 37 distance respondents almost entirely (91.9%) occurred sibling rivalry. Parents treatment can increase the emergence of the impact it had on the children. There are new findings on the impact of self, the impact on siblings and the impact on other people. It is hoped that parents give fair care and affection to their children